Same difference? Translating ‘sensitive texts’ - Wardle, Mary (Vertimo studijos, 2017)
[full article, abstract in English; abstract in Lithuanian]Just like ideas of ‘equivalence’, the concept of ‘sameness’ in translation is not a neutral, univocal one: its interpretation can shift both diachronically and synchronically, with a variety of factors, be they individual or collective, influencing the outcome. This paper intends to investigate a specific example from one author’s work in translation with a view to highlighting the role played by social norms and ideological beliefs in the production and reception of translated texts. Rosamond Lehmann (1901–1990) was an English writer, close to the Bloomsbury Set and author of several popular, critically acclaimed novels. However, her ‘scandalous’ narratives – including extra-marital affairs, gay and lesbian characters and abortion – perhaps rather predictably, provoked some strong reactions in Britain. Although all her books were translated with great success in France, it is perhaps surprising that four of her novels were published in Italy during the years of the Fascist regime. This paper outlines the French and Italian versions of The Weather in the Streets, published in 1936 and 1938 respectively, within their historical context.
Keywords: none